Tuberculous Tenosynovitis Presenting as Ganglion of Wrist - Shahaji Chavan; Shyamsunder Shambhu Sable; Sachin Tekade; Prashant Punia (Case Reports in Surgery)
Tuberculosis (TB) is still endemic in many developed countries. Involvement of the hand and wrist at presentation is extremely rare, and the diagnosis is often missed. A 57 years old male presented with swelling over the left wrist since 3 years Three swellings over dorsal aspect of the left wrist Soft in consistency Non tender Non compressible Mobile at right angles to the plane of the wrist joint. ESR: 45 mm in 1 hr and rest blood investigations were normal. Ultrsonography showed giant cell tumor of Extensor Digitorum sheath. X-ray: soft tissue swelling and MRI was suggestive of extensor tendon sheath extraskeletal synovial Koch’s, or giant cell tumor of tendon sheath. Excision of swelling was planned and intraoperatively, rice bodies were seen inside it. Histopathological examination showed caseous necrosis with granuloma formation. Patient was put on DOT1 therapy. Tuberculous tenosynovitis was first described by Acrel in 1777. Rice bodies occurring in joints affected by tuberculosis were first described in 1895 by Reise. Rice bodies will be diagnosed on plain radiographs when mineralization occurs. More than 50% of cases recur within 1 year of treatment. The currently recommended 6-month course is often adequate with extensive curettage lavage and synovectomy should be performed. Surgery is essential, but the extent of surgical debridement is still debatable. The surgeon has to be aware of the significance of loose bodies when performing routine excision of innocuous looking wrist ganglia.